Detection of different stages of fungal infection in stored canola using near-infrared hyperspectral imaging. (July 2015) - Senthilkumar, T.; Jayas, D.S.; White, N.D.G.
Abstract: Near-infrared (NIR) hyperspectral imaging system was used to detect different stages of fungal infections in stored canola. Artificially infected canola seeds (Fungi: Aspergillus glaucus and Penicillium spp) were subjected to hyperspectral imaging in the range between 1000 and 1600 nm at 61 evenly distributed wavelengths. Four wavelengths 1100, 1130, 1250 and 1300 nm were identified as significant wavelengths and were used in statistical discriminant analysis. Pair-wise, two-class and six-class classification models were developed to classify the healthy and different stages of fungal infected samples. Linear, quadratic and Mahalanobis discriminant classifiers were used to classify healthy, five stages of A. glaucus and five stages of Penicillium spp infected canola seeds. All the three classifiers classified healthy and fungal infected canola seeds with a classification accuracy of more than 95% for healthy canola seeds and more than 90% for the initial stages of A. glaucus and Penicillium spp infected canola seeds. The classification accuracy increased to 100% with increase in fungal infection level (length of time since inoculation). All the samples subjected to imaging were tested for seed germination and free fatty acid value (FAV). The germination decreased with increase in amount of fungal infection, whereas FAV increased with increase in amount of fungal infection. Highlights: The wavelengths 1100 nm, 1130 nm, 1250 nm, 1300 nm were significant to classify healthy and infected canola seeds. The classification accuracy for infected canola seeds ranged from 91.7 to 100%. Quadratic and Mahalanobis classifiers provided better classification accuracy than linear classifier. Germination decreased with increase in time from inoculation by fungi. FAV increased with increase in time from inoculation by fungi.